Hospital Readmission Following Perioperative Acute Myocardial Infarction Associated with Non-Cardiac Surgery - Smilowitz, Nathaniel R. (Circulation, 2018)
BACKGROUND: Acute myocardial infarction (AMI) is a major cardiovascular complication of non-cardiac surgery. We sought to evaluate the frequency, causes, and outcomes of 30-day hospital readmission after perioperative AMI. METHODS: Patients who were diagnosed with AMI during hospitalization for major non-cardiac surgery were identified using the 2014 United States Nationwide Readmission Database. Rates, causes, and costs of 30-day readmissions after non-cardiac surgery with and without perioperative AMI were identified. RESULTS: Among 3,807,357 hospitalizations for major non-cardiac surgery, 8,085 patients with perioperative AMI were identified. A total of 1,135 perioperative AMI patients (14.0%) died in-hospital during the index admission. Survivors of perioperative AMI were more likely to be readmitted within 30-days than surgical patients without perioperative AMI (19.1% versus 6.5%, p<0.001). The most common indications for 30-day rehospitalization were management of infectious complications (30.0%), cardiovascular complications (25.3%), and bleeding (10.4%). In-hospital mortality during hospital readmission in the first 30 days after perioperative AMI was 11.3%. At 6 months, the risk of death was 17.6% and ≥1 hospital readmission was 36.2%. CONCLUSIONS: Among patients undergoing non-cardiac surgery who develop a perioperative MI, approximately 1 in 3 suffer from in-hospital death or hospital readmission in the first 30 days after discharge. Strategies to improve outcomes of surgical patients early after perioperative AMI are warranted.